Evaluasi Kesesuaian Lahan untuk Tanaman Kopi Robusta (Coffea canephora) di Kecamatan Belinyu Kabupaten Bangka - S, Faradis; R, Santi; D, Pratama (Fakultas Teknik dan Teknologi - TANRI ABENG UNIVERSITY, 2025)
Robusta coffee (Coffea canephora) plays an important role in the national economy. Robusta coffee is one type of plantation plant that is widely cultivated by the people in Indonesia, including in Bangka Belitung. Evaluation of land suitability for robusta coffee plants is needed as land use planning that lead to more productive land use. The purpose of this study is to determine the class and distribution of actual and potential land suitability for robusta coffee plants base on order, class and sub-class levels in Belinyu District, Bangka Regency and find out recommendations of land improvement for cultivation of robusta coffee plants in Belinyu District, Bangka Regency. The study was conducted in May – September 2023 located in Belinyu District, Bangka Regency. This research uses survey methods and map analysis. The results showed that from the land area of Belinyu Subdistrict 74,812 Ha, 27,498.5 Ha of land can be developed for robusta coffee plant cultivation. The actual land suitability obtained after soil analysis is 25,781.1 Ha of land included in the S3 (marginally suitable) class and 1,717.4 Ha of land included in the N (unsuitable) class, after land improvement recommendations are made, the potential land suitability of robusta coffee plants in Belinyu District is classified into the S2 (moderately suitable) land suitability class with an area of 21,328.9 Ha, S3 (marginally suitable) 6,165.4 Ha and N (unsuitable) land area of 4.2 Ha. Limiting factors found in the research location are oxygen availability, rooting media, nutrient retention, available nutrients, erosion hazard and flood hazard. Recommendations for land improvement are the use of manure in improving soil physics, the addition of organic materials, liming and terracing